SPATIO-TEMPORAL DYNAMICS OF PHYTOPLANKTON DIVERSITY IN TWO PERENNIAL LENTIC FRESH WATER BODIES OF DHANBAD (JHARKHAND) - Sharmila Kumari; Shailendra Kumar Sinha (The Bioscan, 2024)
Limnological and phytoplankton studies provide crucial insights into the overall health and dynamics of freshwater ecosystems. The present study aims to evaluate limnological characteristics as well as to analyse the phytoplankton community composition of the two selected aquatic environment i.e., Karbala (P1) and Pandey (P2) pond during the study period from November 2020- October 2021. The annual mean values of the key limnological parameters of Karbala (P1) – Pandey Pond (P2) such as, Temperature 26.8ºC – 25.08ºC, EC 1139.58 μs/cm – 736 μs/cm, TDS 968.66 mg/L – 510.42 mg/L, pH 7.4 – 7.36, BOD 5.07 mg/L – 2.26 mg/L, COD 81.35 mg/L – 23.01 mg/L, DO 4.47 mg/L – 6.33 mg/L, Cl- 117.92 mg/L – 40.31 mg/L, Ca2+ 76.28 mg/L – 26.64 mg/L, Mg2+ 28.25 mg/L – 8.71 mg/L, NO - 2.78 mg/L – 1.42 mg/L, PO 3- 1.18 mg/L – 0.99 mg/L respectively,3 4 have been recorded. In the present study, phytoplankton community represented by 4 major classes, i.e., Cyanophyceae, Chlorophyceae, Bacillariophyceae, Euglenophyceae. In P1, the dominated phytoplankton group were observed in the order of Cyanophyceae (40.8 %) > Chlorophyceae (31.3 %) > Bacillariophyceae (26.3 %) > Euglenophyceae (1.7 %). In P2, the phytoplankton group showed the following trend, Bacillariophyceae (43.8 %) > Chlorophyceae (33.1 %) > Cyanophyceae (22.9 %) > Euglenophyceae (0.2 %). The biodiversity indices in both ponds, P1 and P2, the high evenness value of 0.95 and 0.91 respectively, shows an equitable distribution of species, while the Shannon index value indicates a lower to moderate level of species diversity.